Ceramic matrix composites containing carbon nanotubes - Cho, Johann; Boccaccini, Aldo R.; Shaffer, Milo S. P. (Journal of Materials Science, 2009)
Due to the remarkable physical and mechanical properties of individual, perfect carbon nanotubes (CNTs), they are considered to be one of the most promising new reinforcements for structural composites. Their impressive electrical and thermal properties also suggest opportunities for multifunctional applications. In the context of inorganic matrix composites, researchers have particularly focussed on CNTs as toughening elements to overcome the intrinsic brittleness of the ceramic or glass material. Although there are now a number of studies published in the literature, these inorganic systems have received much less attention than CNT/polymer matrix composites. This paper reviews the current status of the research and development of CNT-loaded ceramic matrix composite (CMC) materials. It includes a summary of the key issues related to the optimisation of CNT-based composites, with particular reference to brittle matrices and provides an overview of the processing techniques developed to optimise dispersion quality, interfaces, and density. The properties of the various composite systems are discussed, with an emphasis on toughness; a comprehensive comparative summary is provided, together with a discussion of the possible toughening mechanism that may operate. Last, a range of potential applications are discussed, concluding with a discussion of the scope for future developments in the field. © 2009 Springer Science+Business Media, LLC.
UnivIS-Import:2015-03-09:Pub.2009.tech.IW.LM.cerami